Utilização de vitamina E, selênio e cantaxantina na produção e qualidade de ovos de poedeiras comerciais - Fernandes, Mariane de Oliveira (2016)
The experiment was conducted in an experimental avian located at the Polytechnic School of the Federal University of Santa Maria. The aim of this study was to evaluate the antioxidant effect of vitamin E, Canthaxanthin and Organic Selenium on the quality of stored eggs (0, 7, 14, 21 and 28 days) and production rates of commercial layers from 40 to 55 week of age. In total, 320 hens females of lineage Novogen Brown were distributed in a completely randomized design with 5 treatments with 8 replicates of 8 hens each. The treatments were: T1 (DNC) - Diet Negative control; T2 (DCTX) - Diet with added 6ppm of Canthaxanthin; T3 (DVitE) - diet with 200 ppm of Vitamin E; T4 (DSe) - Diet with 0,4ppm Selenium; T5 (DCTXVitESe) - Diet with added 6ppm of Canthaxanthin + 200ppm of vitamin E + 0,4ppm of Selenium . The experimental phase was divided into four periods of 28 days. The laying rate was significantly affected in hens fed with DSe in the 3rd and 4th period. Hens from DSe and DCTXVitESe had higher egg weight in the 1st period and hens fed with DCTX had better egg weight in the 4th period. The DSe provided a better feed conversion per dozen eggs in the 4th period. The feed conversion by egg mass was better for hens fed DCTX, DSe and DCTXVitESe in the 4th period. Hens fed DCTX and DCTXVitESe had higher egg weight when stored for 28 days in the 1st period. Hens from DCTX had a better percentage yolk in eggs stored for 28 days in the 3rd period and, the 4th period for eggs without storage and in eggs with 14 days of storage. In the 4th period the hens fed with DVitE had a better percentage of yolk and albumen for eggs without storage and in the eggs with 21 days of storage. The albumen percentage was better in eggs with 28 days of storage and without storage from hens fed with DCTX in the 4th period. Hens fed DSe had a better yolk index in eggs stored for 28 days in the 1st period. Eggs of hens had a better yolk color with diets DCTX and DCTXVitESe in all periods. The use of the DSe was better for the variable Unit Haugh of eggs stored for 7 days in the 1st period. The lower content of substances which react with thiobarbituric acid (TBARS) was on egg yolks of the hens fed with DVitE in the 21 days of storage. There were no differences for the variables: feed consumption, body weight, vitelline membrane strength, percentage and thickness of shell, pH of albumen and specific gravity (P>0.05). The use of different additives contributes to improve of production rates and quality of eggs.